2002
DOI: 10.1192/bjp.181.6.494
|View full text |Cite
|
Sign up to set email alerts
|

Stigma by association

Abstract: BackgroundStigma affects not only people with mental illnesses, but their families as well. Understanding how stigma affects family members in terms of both their psychological response to the ill person and their contacts with psychiatric services will improve interactions with the family.AimsTo investigate factors of psychological significance related to stigma of the relatives.MethodIn a Swedish multi-centre study, 162 relatives of patients in acute psychiatric wards following both voluntary and compulsory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
93
0
11

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(112 citation statements)
references
References 17 publications
8
93
0
11
Order By: Relevance
“…Mental illness engenders stigmatising responses in others and leads to discriminatory behaviour, as it carries with it labels of unreliableness, unattractiveness and dangerousness (Pescoscolido et al, 1999;Crisp et al, 2000;Martin et al, 2000;Corrigan et al, 2003). There is evidence of feelings of rejection and attempts at concealment in the relatives of mentally ill in-patients (Phelan et al, 1998;Ostman & Kjellin, 2002), but less is known about the actions of the patients themselves in responding to stigma. Stigma may result in the internalisation of negative beliefs, causing shame and low self-esteem.…”
Section: Discussionmentioning
confidence: 99%
“…Mental illness engenders stigmatising responses in others and leads to discriminatory behaviour, as it carries with it labels of unreliableness, unattractiveness and dangerousness (Pescoscolido et al, 1999;Crisp et al, 2000;Martin et al, 2000;Corrigan et al, 2003). There is evidence of feelings of rejection and attempts at concealment in the relatives of mentally ill in-patients (Phelan et al, 1998;Ostman & Kjellin, 2002), but less is known about the actions of the patients themselves in responding to stigma. Stigma may result in the internalisation of negative beliefs, causing shame and low self-esteem.…”
Section: Discussionmentioning
confidence: 99%
“…I think of myself as a loner even though I'm a caretaker" (Veltman et al, 2002, p. 111). In a Swedish study with family members of mentally ill individuals, 47% of the parents reported feeling as though their child's mental illness led to mental health problems of their own, 33% reported that the child's mental illness affected their ability to have company, and 21% endorsed that at times they believed their mentally ill child would be better off dead (Ostman & Kjellin, 2002). A smaller percentage of these parents (16%) felt that their burden was so heavy that they had suicidal thoughts; and, at times, 14% wished that the patient had never been born (Ostman & Kjellin, 2002).…”
Section: Health Status Of Family Members Of Mentally Ill Individualsmentioning
confidence: 97%
“…This type of stigma is called as courtesy or associative stigma and it comes to the caregivers just by virtue of being associated with the individual with mental illness 17 . Caregivers report depressive symptoms when they are subjected to stigma 15. …”
Section: Introductionmentioning
confidence: 99%